The Effect of Glycosylated Soy Protein Isolate on the Stability of Lutein and Their Interaction Characteristics - Wang, Xia; Wang, Shaojia; Xu, Duoxia; Peng, Jingwei; Gao, Wei; Cao, Yanping (Frontiers in Nutrition, 2022)
Lutein is a natural fat-soluble carotenoid with various physiological functions. However, its poor water solubility and stability restrict its application in functional foods. The present study sought to analyze the stability and interaction mechanism of the complex glycosylated soy protein isolate (SPI) prepared using SPI and inulin-type fructans and lutein. The results showed that glycosylation reduced the fluorescence intensity and surface hydrophobicity of SPI but improved the emulsification process and solubility. Fluorescence intensity and ultraviolet–visible (UV–Vis) absorption spectroscopy results showed that the fluorescence quenching of the glycosylated soybean protein isolate by lutein was static. Through thermodynamic parameter analysis, it was found that lutein and glycosylated SPI were bound spontaneously through hydrophobic interaction, and the binding stoichiometry was 1:1. The X-ray diffraction analysis results showed that lutein existed in the glycosylated soybean protein isolate in an amorphous form. The Fourier transform infrared spectroscopy analysis results revealed that lutein had no effect on the secondary structure of glycosylated soy protein isolate. Meanwhile, the combination of lutein and glycosylated SPI improved the water solubility of lutein and the stability of light and heat.